Minimum Wage Setting: A Comparison of Wage Formulation in Indonesia and Malaysia - Lalu Hadi Adha; Zaeni Asyhadie; Rahmawati (Center for Law and Responsible Business Studies, 2025)
The enactment of wage regulations through Government Regulation (GR) No. 51 of 2023, as an amendment to GR No. 36 of 2021 concerning Wages, raises many different opinions. The government claims that GR No. 51 of 2023 is better than the existing wage regulations in terms of preventing gaps or disparities in minimum wages between regions, therefore the minimum wage of workers will certainly increase in the year 2024. Likewise, the GR No. 51 of 2023 will be the basis in determining the minimum wage for the year 2024 and beyond. Meanwhile, the opinion of workers in on the opposite, the new regulation has the potential to make workers unable to obtain a wage increase in the following year. As several articles contained in GR No. 51 of 2023 is unclear, there may be no increase in the minimum wage. This article aims to analyze the differences and similarities in the wage legal system applicable in Indonesia and Malaysia. Whether the regulations have been able to protect the rights of Indonesian workers, and how to formulate minimum wage setting that can provide protection and legal certainty for workers. This article is doctrinal legal research which by analyses and interpreting the applicable wage rules and regulations, particularly on the determination of the national minimum wage, and comparing them with the wage setting regulations applicable in Malaysia. Similarities and differences is examined in the minimum wage determination rules in Indonesia and Malaysia. It is found that there is a need for an effective regulatory framework that can adapt to the dynamics of the global economy while ensuring adequate protection for all workers.